Phytochemicals of Minthostachys diffusa Epling and Their Health-Promoting Bioactivities - Faraone, Immacolata; Russo, Daniela; Chiummiento, Lucia; Fernandez, Eloy; Choudhary, Alka; Monné, Magnus; Milella, Luigi; Rai, Dilip K (Foods (Basel, Switzerland), 2020)
The genus Minthostachys belonging to the Lamiaceae family, and is an important South American mint genus used commonly in folk medicine as an aroma in cooking. The phytochemical-rich samples of the aerial parts of Minthostachys diffusa Epling. were tested for pharmacological and health-promoting bioactivities using in vitro chemical and enzymatic assays. A range of radical scavenging activities of the samples against biological radicals such as nitric oxide and superoxide anion and against synthetic 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radicals, the ferric reducing antioxidant power and the lipid peroxidation inhibition were determined and ranked using the 'relative antioxidant capacity index' (RACI). The ethyl acetate fraction showed the highest RACI of +1.12. Analysis of the various fractions' inhibitory ability against enzymes involved in diabetes (α-amylase and α-glucosidase), and against enzymes associated with Parkinson's or Alzheimer's diseases (acetylcholinesterase and butyrylcholinesterase) also suggested that the ethyl acetate fraction was the most active. Liquid chromatography-tandem mass spectrometry analysis of the ethyl acetate fraction showed more than 30 polyphenolic compounds, including triterpenes. The inhibitory cholinesterase effects of the triterpenes identified from M. diffusa were further analysed by in silico docking of these compounds into 3D-structures of acetylcholinesterase and butyrylcholinesterase. This is the first study on pharmacological activities and phytochemical profiling of the aerial parts of M. diffusa, showing that this plant, normally used as food in South America, is also rich in health-promoting phytochemicals.
Keywords: polyphenols; relative antioxidant capacity index (RACI); beta-carotene bleaching; flavonoids; Lamiaceae; liquid chromatography–mass spectrometry analysis (UHPLC-MS/MS); DPPH; terpenoids; Minthostachys diffusa